PRECISE MEASUREMENT OF THE ACTIVITY/COMPOSITION RELATIONS OF H2O-N2 AND H2O-CO2 FLUIDS AT 500°C, 500 BARS - Anovitz L.M.; Blencoe J.G.; Joyce D.B.; Horita J. (My University, 1998)
The activity/composition relations of H2O-N2 and H2O-CO2 fluids have been measured at 500°C, 500 bars. The results are more accurate, and much more precise, than any currently available, especially for H2O-poor compositions. Samples were reacted at fixed water activities (0.062 ≤ aH2O ≤ 0.777), using Cu3N as the source of N2, and Ag-oxalate as the source of CO2. After each experiment the masses of water and gas in the samples were analyzed manometrically. Results depend on the value used for the hydrogen fugacity for pure H2O in equilibrium with the oxide buffer, but using a newly measured value for Ni-NiO and fitting the data to a two-parameter Margules equation yields: for H2O-N2 fluids: WG,H2O = 3455.0 J/mol, WG,N2 = 1990.1 J/mol; and for H2O-CO2 fluids: WG,H2O = 3882.5 J/mol, WG,CO2 = 4902.6 J/mol. As uncertainties are not orthogonal, standard errors cannot be given. The data suggest that H2O-CO2 fluids exhibit large positive deviations from ideality at 500°C, 500 bars, in marked contrast to values predicted by available equations of state. These results indicate that more accurate models for both H2O-N2 and H2O-CO2 fluids are needed.